First attempt to assess ecotoxicological risk of fifteen rare earth elements and their mixtures in sediments with diffusive gradients in thin films. (15th October 2020) - Gu, Yang-Guang; Gao, Yan-Peng; Huang, Hong-Hui; Wu, Feng-Xia
Highlights: Probability risk assessment of intertidal sediment REEs in the PRE. DGT-labile light REE concentrations were lower than heavy REE concentrations. The new procedure is effective for evaluating REE mixture toxicity. Potential toxicities for both individual REEs and REE mixtures were identified. Abstract: Rare earth elements (REEs) are emerging contaminants due to their large scale of exploitation worldwide for using in the high-technology sector. Diffusive gradients in thin films (DGT) are a good method to measure the bioaccessibility of inorganic substances. This study is the first to evaluate the combined toxicity of REEs in sediments to aquatic biota using the DGT technique. The intertidal zone of the Pearl River Estuary (PRE) was selected as a case study, as the upper reaches of the Pearl River is a major REE reserve and production region. The DGT-labile measured concentrations of REEs (∑REEs) were found to range from 7.02–16.06 μg/L in intertidal surface sediments of the PRE. Assessment of single REE toxicity found that risk quotient (RQ) values for Y, Pr, Nd, Eu, Dy, Er, and Yb are significantly higher than 1, indicating that the adverse effects of these single REEs should be not ignored. The combined toxicity of REE mixtures based on probabilistic ecotoxicological risk assessment, shows that intertidal surface sediments of PRE had a low probability (3.72%) of toxic effects to aquatic biota. Graphical abstract: Image, graphical abstract